ON THE NEED TO DEVELOP TECHNOLOGIES FOR PRODUCING BIOPLASTICS IN KAZAKHSTAN - Kairat Rizabekovich Uteulin; Kabyl Zhambakin (Academic Journal of Physical and Chemical Sciences, 2020)
This article is published with a purpose to draw attention to the need to initiate in Kazakhstan the development of technologies for producing bioplastics from Kazakhstan’s own renewable plant resources. Every year, Kazakhstan generates hundreds of thousands of tons of plastic waste based on synthetic polymers traditionally produced from petrochemical raw material. Among them are bottles, packaging and bags. For example, in 2019 alone, plastic waste amounted to over 480 thousand tons. 15 companies, including two plastic processing plants, are not capable to cope with this amount of garbage. More than 18 million plastic bags are discarded in Kazakhstan every day, contaminating the environment. Since only about 9% of the plastic produced is recycled, the remaining part either contaminates the environment or is damped where the complete decomposition takes up to 500 years, releasing toxic substances into the soil in the mean time. The production of bioplastics and bioplastics-based products that will decompose in a short time (few months) will reduce the use of synthetic plastic products the decomposition of which is extremely slowly from 100 up to 500 years. Petroleum-based plastic is a real threat as a source of environmental pollution. Kazakhstan is taking measures to reduce environmental pollution. Starting in 2025 it is planned to introduce a complete ban on the realization of petroleum-based food packaging (bags). It is necessary to develop technologies for producing biodegradable polymers from renewable biological resources to replace petroleum-based plastic, reduce environmental pollution and increase global sustainability. There is a need for initiation of the research work on bioplastics in Kazakhstan.